In Vivo Activation of Midbrain Dopamine Neurons via Sensitized, High-Affinity α6* Nicotinic Acetylcholine Receptors - Drenan, Ryan M. (2008)
α6-containing (α6*) nicotinic ACh receptors (nAChRs) are selectively expressed in dopamine (DA) neurons and participate in cholinergic transmission. We generated and studied mice with gain-of-function α6* nAChRs, which isolate and amplify cholinergic control of DA transmission. In contrast to gene knockouts or pharmacological blockers, which show necessity, we show that activating α6* nAChRs and DA neurons is sufficient to cause locomotor hyperactivity. α6(L9’S) mice are hyperactive in their home cage and fail to habituate to a novel environment. Selective activation of α6* nAChRs with low doses of nicotine, by stimulating DA but not GABA neurons, exaggerates these phenotypes and produces a hyperdopaminergic state in vivo. Experiments with additional nicotinic drugs show that altering agonist efficacy at α6* provides fine-tuning of DA release and locomotor responses. α6*-specific agonists or antagonists may, by targeting endogenous cholinergic mechanisms, provide a new method for manipulating DA transmission in Parkinson’s disease, nicotine dependence, or attention deficit hyperactivity disorder.